Empirical Analysis of Green Accounting Practices and Corporate Profitability: A Study Of Selected Oil And Gas Firms - Oyewole Kazeem Adewale; Abdal Ahmed; Joshua Adedapo Daniel; Sulaiman Taiwo Hassan (Insight: Indonesian Journal of Social, Humanity, and Education, 2026)
Nigeria’s oil and gas sector plays a vital role in national economic development but also contributes significantly to environmental degradation through oil spills, gas flaring, and pollution. Although green accounting has been promoted as a mechanism for integrating environmental considerations into corporate decision-making, empirical evidence regarding its effect on firm profitability in developing economies remains limited and inconclusive. This study examines the relationship between green accounting practices and profitability among listed oil and gas companies in Nigeria by assessing the effects of audit size (AS), environmental audit reporting (EAR), and environmental damage and litigation (EDL) on earnings per share (EPS). The study employs a quantitative research design using secondary panel data obtained from the published annual reports and sustainability reports of selected listed firms. Data were analysed using descriptive statistics, correlation analysis, and panel data regression techniques. The findings reveal that AS, EAR, and EDL have positive but statistically insignificant effects on EPS (p > 0.05), indicating that current green accounting practices do not significantly enhance corporate profitability in the Nigerian oil and gas industry. This study contributes to the environmental accounting literature by providing empirical evidence from an emerging economy using a specific set of green accounting proxies that have received limited attention in prior research. The findings suggest that stronger regulatory enforcement, standardized environmental reporting, and greater integration of environmental costs into corporate governance are necessary to improve the effectiveness of green accounting practices and promote sustainable financial performance.